ANALISIS FAKTOR-FAKTOR KETERLAMBATAN PADA PROYEK PEMBANGUNAN EXPAND & ENHANCEMENT NEUCENTRIX PUGERAN YOGYAKARTA MENGGUNAKAN SPSS - Pinuji, Putri; Permata Suwandi, Putri Anggi; Rizani, Mohammad Debby (Universitas PGRI Semarang, 2025)
The 2023 Neucentrix Expand Enhancement Development Project Pugeran Yogyakarta is planned to last 19 weeks. However, there was a delay due to the large amount of additional work and new items that were not listed in the BoQ. This research aims to identify the main factors causing project delays. The data used came from a questionnaire and then factor analysis was carried out using SPSS. A total of 11 managerial team respondents filled out the questionnaire, producing 18 valid variables that were very reliable. The results of the analysis show 5 rankings of the main factors causing delays, namely: delayed payments have an impact on project delays; changes in costs due to additional work; less than optimal labor productivity; error in basic price estimation in the Cost Budget Plan; difficulty in finding materials and/or equipment due to certain specialties; submission and request for changes to completed work from the project owner; changes in work methods by contractors; lack of adequate workforce; owner's delay in making decisions; changes to the scope of work (SOW) during implementation; and lack of workforce discipline regarding attendance and attendance, which hampers work time